Land Problems and Legal Impact for Agrarian and Spatial Planning Officers - Syahr, Zulfia Hanum Alfi; Hakim, Muh. Ridha; Utomo, Nurrahman Aji; Wismayanti, Yanuar Farida; Ansyah, Rahmat Husein Andri; Sally, Novian Uticha (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) is a government institution with the authority to carry out duties and functions of public services in agrarian, spatial planning and land. The development of land law issues in society has involved many officials from the Ministry of ATR/BPN as implementers of agrarian and land sector functions. The impact is the emergence of a sense of anxiety and worry felt by the Ministry of ATR/BPN officials when carrying out their duties. It is because if the land administration services provided by the Ministry of ATR/BPN are not thorough and careful, there are many gaps in legal violations, not only administrative and civil but also criminal. If the implementer of agrarian and land functions is a Civil Servant (PNS) and becomes a suspect in a legal case, he will be temporarily dismissed. He will not receive income from the Government Regulation on Civil Servant Management. Therefore, the problem that will be studied in this paper is the legal impact of land problems on the implementers of agrarian functions. This study explores the potential legal risks that implementers of agrarian functions can experience amidst the development of problematic land issues. The method used in this study is qualitative with a normative juridical approach. A normative juridical approach examines the legal rules and regulations that apply to answer legal problems. The results are that the administrative services carried out by the Ministry of ATR/BPN cannot be seen solely as part of administrative law. This is because the administrative services carried out can impact a person's legal ownership/civil status. Existing law enforcement instruments differentiate the judicial process for administrative, civil, and criminal violations.